Simulasi Pencitraan Ultrasonografi (USG) Menggunakan PdeTool Matlab - Anam, Choirul (BERKALA FISIKA, 2009)
Diagnostic imaging with ultrasound is based on the mechanical properties of an object. To evaluate how the ultrasound wave propagates in an object and imaging of the object, can be done with simulation techniques. Simulation of ultrasound wave propagation was performed using Matlab pdetool. The simulation was conducted to determine the image quality due to the influence from variation of the object, variations in the number of objects, various types of objects and variations in frequency of the signal. From the simulation showed that the ellipse and box objects can be distinguished. If the number of object is increased, will cause the image more complex. This happens because the waves are about an object, it would interfere with ultrasound waves that will be used to image the next object. If two objects have different c is high enough, then the imagery on the field boundary of two mediums was very clear. Conversely, if the difference is very small c, then the boundary of two mediums were not visible. If the frequency rises, causing axial resolution increase, but cause increased attenuation. Â Keywords: USG, Simulation, pdetool Matlab